Gestational malaria - Purizaca Benites, Manuel (2015)
Gestational malaria is a distinct clinical entity. Due to the presence of the placenta and fetus the clinical and laboratory findings have their own characteristics that differentiate it from adults’ malaria. There are alterations in the woman's body and the placenta that affect to a greater or lesser degree to the fetus that is exposed to vertical transmission. Both treatment and prognosis are somewhat different. In this paper we present important aspects of this new clinical entity that deserves a special approach.